2017
DOI: 10.1111/oik.03670
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of litter decomposition rates in a tropical forest: functional traits, phylogeny and ecological succession

Abstract: Plant litter decomposition is one of the most important processes in terrestrial ecosystems, as it is a key factor in nutrient cycling. Decomposition rates depend on environmental factors, but also plant traits, as these determine the character of detritus. We measured litter decomposition rate for 57 common tree species displaying a variety of functional traits within four sites in primary and four sites in secondary tropical forest in Madang Province, Papua New Guinea. The phylogenetic relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 79 publications
2
27
0
1
Order By: Relevance
“…Similarly, stem traits such as low stem‐specific density (SSD) also (indirectly) relate to fast leaf litter decomposition (Szefer et al. ). The species‐level link between leaf traits and litter decomposition has also been shown to translate to the community level, with community‐weighted mean (CWM) traits relating to decomposition rates of the community litter (Garnier et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, stem traits such as low stem‐specific density (SSD) also (indirectly) relate to fast leaf litter decomposition (Szefer et al. ). The species‐level link between leaf traits and litter decomposition has also been shown to translate to the community level, with community‐weighted mean (CWM) traits relating to decomposition rates of the community litter (Garnier et al.…”
Section: Introductionmentioning
confidence: 99%
“…In an increasingly globalized world, the number of alien plant species invading plant communities continues to rise (van Kleunen et al 2015). One major concern is that invasive alien species will lead to significant changes in functioning of the invaded ecosystem (e.g., Dassonville et al 2008, Py sek et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decomposition rates have been shown by several previous studies to be greatly reduced when tropical forests are converted to anthropogenic pasture or agricultural use (Lorenzo et al., ; Paudel et al., ; Szefer et al., ). Our study similarly revealed reduced decomposition rates in anthropogenic pasture compared to forest.…”
Section: Discussionmentioning
confidence: 96%
“…(); (3) Szefer et al. (); (4) Paudel et al. (); (5) Barlow, Gardner, Ferreira & Peres, (); (6) Xuluc‐Tolosa, Vester, Ramırez‐Marcial, Castellanos‐Albores & Lawrence (); (7) Ewel (); (8) Mendoza, Gallardo, Turrion, Pando & Acenolaza (); (9) Ostertag, Marin‐Spiotta, Silver & Schulten (); (10) Vasconcelos & Laurance (); (11) Barajas‐Guzmán & Alvarez‐Sánchez (); (12) Gove et al.…”
Section: Discussionmentioning
confidence: 99%